Noise characteristics of a superlattice avalanche photodiode - Chakrabarti P.; Choudhury S.C.; Pal B.B. (My University, 2025)
The noise generated due to randomness of multiplication process in the avalanche region of an AlxGa1-xAs/GaAs quantum well p+-i-n+ structure has been studied. The paper presents a quantitative evaluation of the noise performance of the superlattice APD which has not been done so far. Further, useful design data for low noise structure is given. © 1989 Springer-Verlag.